미용소비가치가 미용실 이용동기와 점포선택기준에 미치는 영향 - 박보연; Park Bo-yeon; 유태순; Yoo Tai-soon (한국디자인포럼, 2016)
연구배경 본 연구는 미용실 고객들을 대상으로 미용소비가치가 미용실 이용동기와 점포선택기준에 미치는 영향과 미용실 고객들의 이용동기와 점포선택기준 간의 연령별 차이를 알아보고자 한다. 또한 연구를 기초 하여 미용 소비가치를 이해하고 연령별 고객의 차이점을 자료로 제공하여 미용실 영업활성화를 위한 마케팅 전략 수립에 필요한 자료를 제시하는데 의의가 있다. 연구방법 대구지역에 거주하는 만 20세에서 50세 이상의 성인여성 490명을 대상으로 하였으며, 자료 분석은 SPSS 23.0 통계 프로그램을 이용하여 다중회귀분석을 실시하였고, 일원배치 분산분석을 실시하여 사후검증으로 Duncan-test를 실시하였다. 연구결과 첫째, 사회적, 감정적, 기능적가치는 정기이용에 정적인 영향을 미쳤다. 둘째, 기본선택을 할수록 감정적, 기능적 가치의 영향을 많이 받았고, 물리적 선택을 많이 할수록 기능적 가치에 영향을 많이 받는 것으로 나타났다. 셋째, 기본 선택을 하는 경우 정기 이용과 특별이용이 높았고, 물리적 선택과 고급선택을 하는 경우 특별이용 보다 정기이용이 높았다. 넷째, 연령별 차이에서는 사회적, 기능적가치가 통계적으로 유의한 차이가 있는 것으로 나타났다. 특히 40대의 사회적, 기능적가치가 가장 높았다. 결론 고객의 미용소비가치가 미용실의 이용동기와 점포선택기준에 영향을 미치는 것으로 나타났다. 특히 40대고객이 가장 민감한 반응을 보이는 것으로 나타났다. 향후 고객의 미용소비가치와 연령별 차이를 더욱 심층적으로 연구하고, 이를 활용하기 위한 방안을 찾기 위한 노력이 필요하다. Background The objective of this study is to understand the influence of beauty salon clients beauty consumption value on the current status of beauty salon usage and the store choice criteria, also to examine differences between beauty salon clients usage motivation and store choice criteria depending on their age. The significance of this study is to suggest useful data necessary to establish marketing strategies to vitalize the beauty salon sales. Methods Targeting female adults(20-more than 50 year) residing in Daegu. Total 460 questionnaires were used for the final analysis. And then the survey data was analyzed usage SPSS 23.0. Result First, social, emotional, and functional values of priority made a significant impact on the regular visits. Second, As basic choices were made, emotional and practical values became important. As physical choices were made, a practical value increased. Third, in case basic choices were chosen, regular visits and special usages increased. Also, as for physical and luxurious choices were made, physical usages were higher than the regular visits. Fourth, so far as the age difference goes, social and practical biases were observed; women in their 40`s revealed that they prioritize social and practical values as they make their choices. Conclusion beauty consumption value has deeply influenced their choosing of a specific beauty shop. Particularly, customers in their 40`s showed the most distinctive preference. The future study needs done to delve into the difference among the age groups in depth. Furthermore, the ways to implement these findings to actual business plan should be ventured.